Steriodal saponins from the rhizomes of Tupistra chinensis Baker. (March 2023) - Lu, Yunyang; He, Xuefeng; Liu, Yang; Cao, Yu; Qiu, Pengcheng; Yuan, Xiaofeng; Lu, Qiangqiang; Tang, Haifeng; Yang, Hua
Abstract: Chemical constituent investigation on the n -BuOH extract of the rhizomes of Tupistra chinensis Baker leads to the isolation of ten compounds including eight undescribed furostanol saponins, tupischinosides A − H, and two known ones. The structures of isolated compounds were determined by extensive spectral analysis and chemical evidences. Interestingly, tupischinosides A and B, C and D, E and F, G and H were identified as four pairs of epimers. The cytotoxicity of tupischinosides A − H against human cancer cell lines U87, SHG44, U251, LN229 and HepG-2 was evaluated by CCK-8 method. As a result, tupischinosides A and C exhibited significant proliferation inhibitory effect on the tested cancer cells. On the contrary, the corresponding epimers, tupischinosides B and D, which only differ in the configuration of C-23 didn't exhibit any cytotoxicity to cancer cells. These results indicated that the stereochemistry of C-23 was crucial to the activity of the compounds. Graphical abstract: Eight undescribed furostanol saponins along with two known ones were isolated from the rhizomes of Tupistra chinensis Baker. The cytotoxicity against human cancer cell lines U87, SHG44, U251, LN229 and HepG-2 was evaluated. Image 1 Highlights: Eight undescribed furostanol saponins were isolated from the rhizomes of Tupistra chinensis. Tupischinosides A – H were identified as four pairs of epimers. The configuration of the substituent at C-23 of the side chain was determined. The cytotoxicity between the epimers tupischinosides A and B, C and D was totally different.